Evaluating the Link between Oil Price and Macroeconomic Dynamics in Nigeria - Magaji, Sule; Musa, Ibrahim; Ismail, Yahaya (New Advances in Business, Management and Economics Vol. 5, 2025)
Crude oil exports have long been a major source of foreign exchange earnings and government income for the Nigerian economy. The volatility of the oil price and its impact on Nigerians’ economic well-being are among the country’s most pressing issues at the moment. This research explores the link between oil price fluctuations on selected macroeconomic variables in Nigeria by analyzing quarterly data from 1980 to 2022, covering a span of 42 years. The data was collected from the National Bureau of Statistics (NBS) publications, the Central Bank of Nigeria (CBN) Annual Report and Statistical Bulletin, World Bank and International Financial Statistics (IFS) of the IMF. The chosen macroeconomic indicators include Real Gross Domestic Product, Consumer Price Index, and Real Exchange Rate. The Vector Error Correction Model (VECM) was employed for analysis, and the estimation results indicated long-term interdependencies, where oil price shocks significantly influence the Real Gross Domestic Product, Consumer Price Index, and Real Exchange Rate in Nigeria. The study concluded that crude oil sales serve as the primary source of revenue and foreign earnings for Nigeria, making the economy heavily dependent on global oil prices. Consequently, most macroeconomic indicators are directly or indirectly affected by oil price fluctuations. Given that Nigeria lacks control over oil prices, the study recommended economic diversification to mitigate the adverse effects of external shocks. Specifically, the country should expand its exports beyond oil to non-oil sectors. Diversifying the economy and broadening the oil revenue base would help reduce dependence on crude oil and petroleum products. Implementing sustainable policies, which could help to improve agriculture and industrial sectors, will further shield the economy from the impact of oil price shocks.